Household factors associated with breastfeeding practice among children in Southern Thailand - Supriatin, Supriatin; Hattapradit, Faron; Mamahit, Adi Yeremia; Heri, Mochamad; Iswahyudi, Iswahyudi; Suyitno, Suyitno; Maretalinia, Maretalinia (International Journal of Public Health Science (IJPHS), 2024)
Breastfeeding is an important process for infants including their nutrition, immune system support, digestibility, bonding, convenience, and cost-effectiveness. The breastfeeding rate in Thailand is low compared to Asian countries, but the rate is high for Southern Thailand. This study aimed to examine the household factors (religion) associated with breastfeeding practices in the household in Southern Thailand. This study used secondary data multiple indicators cluster survey (MICS) in 2022. The final sample of this study was 1,176 children under two years. The univariate, bivariate (Chi-square), and multivariate (binary logistic regression) were done using STATA version 17. The percentage of ever breastfed was high which was 97%. The factors of religion (AOR 3.45 95% (1.55–7.69)) and secondary school of education level of the household head (AOR 0.32 95% (0.15–0.67)) were found significantly associated with ever breastfeeding practice. There is a powerful role of religious leaders to empower women to breastfeed infants according to social and religious perspectives.